Corporate Citizenship and Workplace Democracy in Botswana: Rhetoric or Reality? - Langtone Maunganidze (Palgrave Macmillan, Cham, 2022)
Based on the experiences of selected firms in Botswana, this chapter examines the intersection between corporate citizenship and workplace democracy. Despite the growing popularity of the social responsibility discourse and its practices, its application has generally left out one of the most important stakeholders—the workers. Over the years, corporate social investments have tended to focus more on external than internal stakeholders. The rhetoric of good corporate citizenship conceals prevailing inequalities and potential labour rights abuses in most firms. There has been a limited attempt by the corporate sector in Botswana, to genuinely extend corporate citizenship to the workplace.